2022
DOI: 10.3390/jcm11216323
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barré Syndrome in Northern China: A Retrospective Analysis of 294 Patients from 2015 to 2020

Abstract: Objectives: Acute motor axonal neuropathy (AMAN) was first reported to be the main subtype of Guillain–Barré syndrome (GBS) in northern China in the 1990s. About 30 years has passed, and it is unknown whether the disease spectrum has changed over time in northern China. We aimed to study the epidemiological, clinical, and electrophysiological features of GBS in northern China in recent years. Methods: We retrospectively analyzed the medical records of GBS patients admitted to the Second Hospital of Hebei Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Bulbar dysfunction predicted respiratory failure in several studies [4–10, 15–18, 20, 23–27, 33, 36]. Our study confirms bulbar and neck weakness as significant predictors of MV.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Bulbar dysfunction predicted respiratory failure in several studies [4–10, 15–18, 20, 23–27, 33, 36]. Our study confirms bulbar and neck weakness as significant predictors of MV.…”
Section: Discussionsupporting
confidence: 82%
“…Guillain−Barré syndrome (GBS) is a rapidly progressive, auto-immune polyradiculoneuropathy [1][2][3][4][5][6][7]. During the acute phase, patients may develop respiratory failure, eventually requiring mechanical ventilation (MV) [2,[4][5][6][7][8][9][10][11][12][13][14]. Early prediction of respiratory insufficiency is important to correctly triage the patients for appropriate level of care and to prevent complications related to delayed intubation [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Netto and colleagues found that older age, dysautonomia, and pulmonary complications were predictors of mortality in MV patients with GBS [40]. Zhai and their colleague [11] found that HDS (at admission), dysphagia, and dysautonomia were independent risk factors for GBS patients requiring MV. Hyponatremia occurred in 19 (30.6%) patients and was significantly correlated with HDS and ONLS outcomes (p = 0.002, p = 0.001, respectively) and was considered as a predictor of poor prognosis, consistent with previous studies [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found a relationship between outcome and recent preceding infections (antecedent events), clinical presentation, electrophysiological subtype and laboratory findings [6][7][8][9]. Yao and colleagues studied the clinical presentation of GBS in four regions of China and found that a higher proportion of the axonal subtype in central and southwest China; progression in the latter region was more served at nadir and patients had the longest hospital stay [10] Zhai and their colleagues [11] in their retrospective study of 294 patients with GBS found that the AMAN subtype was predominant in northern China (40.1%) and had shorter time to nadir, with prolonged hospitalization, and worse prognosis at discharge than AIDP. A higher GDS score on admission was a strong predictor for poor outcome at discharge and short-term follow-up, independent of treatment type or in-hospital management (Ruiz-Sandoval and their colleagues) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation